Estudo do potencial terapêutico do (E)-1-(BENZO [D] [1,3] DIOXOLS-IL)-3-(3-BROMO-4-ETOXI-5-MET OXIFENIL) PROP-2-EN-1-ONA frente a Leishmania braziliensis: produção de ROS, interação molecular e efeito potencializador da forma nanoparticulada - Linhares, Gleice Rayanne da Silva (2025)
Leishmaniasis is characterized as a neglected tropical disease that represents a major public health problem. In Brazil, Leishmania braziliensis is the main species causing the mucocutaneous form of the disease. The available therapeutic arsenal has important limitations, such as high toxicity, parasite resistance and prolonged therapeutic regimens. Faced with these challenges, chalcones emerge as promising candidates due to their low toxicity in mammalian cells and modulation of oxidative pathways of the parasite. In this context, the objective of the present study was to investigate through in silico and in vitro tests the leishmanicidal potential of four novel synthetic chalcones against L. braziliensis, the influence of FERAI on the production of reactive oxygen species (ROS), intermolecular interactions with possible enzymatic targets and a probable potentiation of the effects with the encapsulated form of FERAI. For this purpose, the computational tools PASS filter, MolPredictX, Molegro Virtual Docker (MVD) 6.0 and GROMACS were used for in silico tests. The antileishmanial activity evaluations, cytotoxicity assays and determination of ROS modulation were performed through in vitro tests. The characterization of the nanoparticles was performed by Zetasizer Lab. The prediction studies indicated a probable activity of the four chalcones against L. braziliensis. In the in vitro study, FERAI showed potent leishmanicidal activity for both L. braziliensis promastigotes and amastigotes, with low cytotoxicity (CC50 > 50 μM), significantly reducing infection in murine macrophages. ROS assays revealed an increase in ROS levels in a concentration-dependent manner, indicating the induction of a redox imbalance as one of the mechanisms of action. Molecular docking studies identified trypanothione reductase (TryR) and dihydroorotate dehydrogenase (DHODH) as potential targets. FERAI-NANO demonstrated low cytotoxicity (CC50 > 50 μM) and an antileishmanial activity approximately 1.15 times higher in L. braziliensis promastigotes (EC50 of 12.25 ± 0.12 μM) when compared to free FERAI (EC50 of 14.08 ± 0.5 μM). Furthermore, FERAI- NANO prevents both infection and the number of amastigotes in infected murine macrophages. It is concluded that FERAI represents a promising candidate as a new antileishmanial drug, combining selectivity, multifactorial mechanism of action and potential for optimization by nanoencapsulation.